Analisis Penggunaan Tenaga Kerja Lokal Pada Proyek Konstruksi - Alexander Adnan Hans Duha; Jun Fajar Krisman Giawa; Jefri Rahmat Daeli; Hamedoni Harita (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the utilization of local labor in construction projects in the Nias region and to identify the factors influencing their level of involvement. The research employs a descriptive quantitative approach, with data collected through questionnaires, interviews, and field observations. The sample was selected using a purposive sampling technique, involving construction workers, contractors, and project supervisors. Data analysis was conducted using descriptive statistics and factor analysis to determine the dominant factors affecting the use of local labor. The results indicate that the level of local labor involvement falls into a moderate category, accounting for approximately 60–70% of the total project workforce. The primary factor influencing the use of local labor is workforce competence, followed by contractor policies, education and training levels, as well as geographical and socio-cultural conditions. The use of local labor has a positive impact on increasing community income and employment opportunities; however, challenges remain in terms of work quality due to limited skills. This study concludes that optimizing the use of local labor requires improving competencies through training and certification, as well as strengthening policies that support local workforce empowerment. Synergy between the government, contractors, and the community is essential to achieving inclusive and sustainable construction development in the Nias region.